Repair of Orbital Floor Fracture With Modified Transnasal Endoscopic Approach Through Anterior Space to Nasolacrimal Duct - Suzuki, Motohiko (J Craniofac Surg, 2017)
OBJECTIVES: Endoscopic approach provides excellent magnification and visualization, and a purely transnasal approach is minimally invasive method. However, it is very difficult to repair anterior and lateral fractures with the previous transnasal endoscopic approaches, since repair of orbital fractures is managed through the middle meatus and ostium from the posterior side of the nasolacrimal duct with side-viewing endoscope and curved instruments. Therefore, the authors used modified transnasal endoscopic approach as an alternative for repair of orbital floor fractures in order to effectively reach the lateral or anterior fracture of the orbital floor with straight endoscope and instruments endoscopically. METHODS: Modified transnasal endoscopic approach through anterior space to nasolacrimal duct was performed in patients with orbital floor fracture, when patients rejected extranasal approach and reconstruction could not be performed by the previous purely transnasal endoscopic approach. After removal of the medial maxillary bone, the lateral wall of nose was shifted in the medial direction to allow wider access to the maxillary sinus. The bone fragments entrapping the orbital content are removed carefully, and correction of periorbita is performed. After surgery, patients were asked whether they have symptoms and/or complications. RESULTS: This modified approach was performed in 15 patients (10 males and 5 females). Mean age at surgery was 37.6 years with a range between 17 and 67. Double vision disappeared in all patients. CONCLUSIONS: This novel approach appears to be a safe and effective technique for the repair of orbital floor fractures.